Suspected natural lysosomal storage disease from ingestion of pink morning glory (Ipomoea carnea) in goats in northern Argentina - Ríos, Elvio E. (2015)
This study describes an occurrence of pink morning glory (Ipomoea carnea) intoxication in goats in northern Argentina. The clinical signs displayed by the affected animals were ataxia, lethargy, emaciation, hypertonia of the neck muscles, spastic paresis in the hind legs, abnormal postural reactions and death. The clinico-pathologic examination revealed that the affected animals were anemic and their serum level of aspartate aminotransferase was significantly increased. Cytoplasmic vacuolation in the Purkinje cells and pancreatic acinar cells was observed by histological examination. The neuronal lectin binding pattern showed a strong positive reaction to WGA (Triticum vulgaris), sWGA (succinylated T. vulgaris) and LCA (Lens culinaris). Although I. carnea is common in tropical regions, this is the first report of spontaneous poisoning in goats in Argentina.